Circadian rhythm of blood pressure and energy state patients` with essential hypertension and type 2 diabetes mellitus - Sytina, Irina (My University, 2013)
Purpose: To study changes in the circadian rhythm of blood pressure (BP) and energy supply peculiarities patients’ with essential hypertension (EY) and type 2 diabetes mellitus (DM). Materials and methods: 50 patients with EH and DM, (57,6±7,6 years, females 41 (55%) males 32 (44%)) were examined. All patients were conducted with daily monitoring of blood pressure (DMBP). Energy status was assessed in terms of adenine nucleotides (ATP, ADP, AMP) in red blood cells. Results: According to DMBP the circadian rhythm of BP was assessed. The results revealed that patients with EH and DM, non-dipper profile had 41.3% of evaluated, profile night-peaker -29,5%, over-dipper - 6,9%, saving physiological rhythm was observed in 22.3% of individuals. In assessing the level of ATP, AMP, ADP - as markers of organism energy supply, was found. Individuals with preserved physiological rhythm of BP (dipper), had sufficient level of energy subsistence (ATP - 1.5 mmol / l [1.5; 1.3 mmol / L], AMP-1.28 mmol / L [1.4, 1.3 mmol / L], ADP 1.38 mmol / L [1.6, 1.42 mmol / L]) the macroergic compounds in the group with non-dipper- faced substantial changes - ATP -1.24 mmol / L [1.18, 1.43 mmol / L], when simultaneous level increasing of AMP-1, 61mmol / L [1.57, 1, 7mmol / L] and ADP-1, 46mmol / L [1.3, 1.57 mmol / L], and patients with night-peaker - ATF-1, 29mmol / L [1.24, 1.33 mmol / l] AMP -1.7 mmol / L [1.68, 1.71 mmol / L], in the group with over-dipper -ATP levels tended to reduce, but it was not reliable in comparison with the group dipper - (p = 0,56). Conclusion: The results disclose that 77.7% of patients with EH and DM, had a deranges of the circadian rhythm, mainly due to the non— dipper, and and night peaker. It are characterized by development of energy deficient state, which is evidenced by reducing of ATP level, with AMP and ADP increasing simultaneously.